Konsep Nusantara Dalam Politik Ekspansi Gajah Mada: Fondasi Geopolitik Indonesia Modern - Yasa, Putu Dana (Sphatika: Jurnal Teologi, 2025)
Politics and leadership is a discourse that is always interesting to discuss until now. The discourse on politics has existed since ancient times, we know several great figures who serve as role models in the development of the political system, especially in the perspective of Hinduism. One of the great figures whose name is still so revered today is Patih Gajah Mada with a huge political movement to unite the archipelago. This research was conducted with the aim of re-examining the political values that developed in Hindu civilization in the archipelago. This research uses a qualitative approach that conveys the results of research in the form of narratives with the support of various sources that are relevant to this research. In this research we can see the big name of Patih Gajah Mada has an important role in the unification of the archipelago which we know is so diverse, this unification cannot be separated from the application of noble political values and is able to become a guideline in building a political system in the Kali Yuga era today